Transformational Politics. New networks of governance - Crowley, D. (The transformational wave: Beyond Covid-19, 2021)
Species wise, its simple: Adapt or Die. The chapter identifies New Networks of Governance as the base of a growing Transformational Politics that could facilitate the urban transition to adequately respond to the existential threat Climate Emergency poses. The author has used a Participatory Action Research method inspired by Social Ecology principles, the text is a footnote from ongoing activities trying to implement strategies described herein. The introduction outlines why a Transformational Politics is needed, the economic roots of Climate Breakdown and responses since the 1999 actions that “permanently changed the political landscape of globalisation”. Section 1, “Municipalist Solutions”, examines current Citizen-Led Initiatives and governance models that could enable a scaling up of the existing Global Ecovillage Network model so that “Every city can be a green city”, including; the feminist revolution in Rojava, Syria; an eco-neighbourhood in São Paulo, Brazil and use of Peoples Assemblies in Extinction Rebellion urban occupations. Section 2, “Lessons from Spain”, examines the ongoing feminist democratic revolution in Spain’s Rebel Cities from 2015 and their development into a global Fearless Cities network since 2017. Dynamics from 2011’s Spanish Revolution assemblies are examined in greater detail. The Conclusions offers suggestions for readers and community groups.